Silent Corticotroph Staining Pituitary Neuroendocrine Tumors: Prognostic Significance in Radiosurgery - Maragkos, Georgios A; Mantziaris, Georgios; Pikis, Stylianos; Chytka, Tomas; Liscak, Roman; Peker, Selcuk; Samanci, Yavuz; Bindal, Shray K; Niranjan, Ajay; Lunsford, L Dade; Kaur, Rupinder; Madan, Renu; et al. (Neurosurgery, 2023)
BACKGROUND AND OBJECTIVES: There is conflicting evidence on the significance of adrenocorticotrophic hormone (ACTH) staining in the prognosis of nonfunctioning pituitary neuroendocrine tumors (NFpitNETs). The objective of this study was to define the effect of ACTH immunostaining on clinical and radiographic outcomes of stereotactic radiosurgery (SRS) for NFpitNETs. METHODS: This retrospective, multicenter study included patients managed with SRS for NFpitNET residuals. The patients were divided into 2 cohorts: (1) silent corticotroph (SC) for NFpitNETs with positive ACTH immunostaining and (2) non-SC NFpitNETs. Rates of local tumor control and the incidence of post-treatment pituitary and neurological dysfunction were documented. Factors associated with radiological and clinical outcomes were also analyzed. RESULTS: The cohort included 535 patients from 14 centers with 84 (15.7%) patients harboring silent corticotroph NFpitNETs (SCs). At last follow-up, local tumor progression occurred in 11.9% of patients in the SC compared with 8.1% of patients in the non-SC cohort (P = .27). No statistically significant difference was noted in new-onset hypopituitarism rates (10.7% vs 15.4%, P = .25) or visual deficits (3.6% vs 1.1%, P = .088) between the 2 cohorts at last follow-up. When controlling for residual tumor volume, maximum dose, and patient age and sex, positive ACTH immunostaining did not have a significant correlation with local tumor progression (hazard ratio = 1.69, 95% CI = 0.8-3.61, P = .17). CONCLUSION: In contemporary radiosurgical practice with a single fraction dose of 8-25 Gy (median 15 Gy), ACTH immunostaining in NFpitNETs did not appear to confer a significantly reduced rate of local tumor control after SRS.
Keywords: nádory hypofýzy; Humans; neuroendokrinní nádory; výsledek terapie; lidé; Neuroendocrine Tumors; adrenokortikotropní hormon; radiochirurgie; kortikotropní buňky; Radiosurgery; Pituitary Neoplasms; Follow-Up Studies; Retrospective Studies; prognóza; Treatment Outcome; retrospektivní studie; Corticotrophs; Prognosis; následné studie; Adrenocorticotropic Hormone